Terezka Drnzik interviewed by Claudia Taranto in Interview with six belly dancers collection - Drnzik, Terezka; Taranto, Claudia; ABC Radio (Australia) (1989)
Drnzik speaks of first seeing belly dancing at a Greek wedding; beginning to learn from a Syrian teacher; practising; performing Danse Orientale; her attraction to belly dancing; spiritual nature of the dance; dancing to an audience; differences in Western & Middle Eastern audiences; her students; music; Western responses to the dance; movements; European performances; venues; tipping; dance variation within Arab world; musical instruments; history of belly dancing; role of dance in Arabic culture; earthy quality of the dance; performing; attitudes to dancers; reasons for giving up performing; teaching; concerts; effect of Lebanese unrest on Australian Lebanese; closure of Lebanese nightclubs, Sydney; future of dance in Middle East; shimmy (dance movement); costumes.
Recorded, for broadcast on the ABC Radio program The Listening Room on 18 September 1989.
Recorded on 18 September 1989 in Sydney, N.S.W.
Digital master available
Terezka Drnzik, belly dancer and oriental dance teacher
Keywords: Drnzik, Terezka -- Interviews; Dancers -- Australia -- Interviews; Dance teachers -- Australia -- Interviews; Belly dance -- Australia; Belly dance -- Study and teaching -- Australia; Alsharqi (Dance) -- Australia